Analysis of factors influencing purchase intention - Fahlevi, Renza; Giorgyna, Giorgyna; Sinambela, Fitriana Aidnilla (Jurnal Fokus Manajemen Bisnis, 2024)
Currently, the use of counterfeit products in Indonesia is increasing. Handbags are among the most widely used counterfeited products. This study aims to measure consumer behavior when purchasing fake bags. Research data were obtained by distributing questionnaires to 240 potential consumers who used counterfeit handbags. The collected data were processed using the Smart PLS software. This study found that novelty seeking, status consumption, and brand consciousness shape attitudes toward counterfeit products, whereas perceived risk and integrity have no bearing on these attitudes. Additionally, perceived risk, brand consciousness, and attitude toward counterfeit products directly influence purchase intention, whereas novelty seeking, status consumption, and integrity do not impact purchase intention. Notably, a significant influence on purchase intention was observed when mediated by attitudes toward counterfeit products in the case of novelty seeking and status consumption. However, perceived risk, integrity, and brand consciousness do not influence purchase intention when mediated by attitudes toward counterfeit products.